Glycolysis-Derived Compounds From Astrocytes That Modulate Synaptic Communication - Gonçalves, Carlos-Alberto; Rodrigues, Letícia; Bobermin, Larissa D.; Zanotto, Caroline; Vizuete, Adriana; Quincozes-Santos, André; Souza, Diogo O.; Leite, Marina C. (Frontiers in Neuroscience, 2019)
Based on the concept of the tripartite synapse, we reviewed the role of glucose-derived compounds from glycolytic pathways in astroglial cells. Glucose provides energy and substrate replenishment for brain activity, such as glutamate and lipid synthesis. In addition, the glucose metabolism, carried out in the astroglial cytoplasm, result in products such as lactate, methylglyoxal, and glutathione (GSH), which modulate receptors or channels in neurons. Glucose has four potential destinations in neural cells and it is possible, didactically, to conceive a crossroad in “X” to analyze their four destinations. Glucose-6P can be used either for glycogen synthesis or the pentose phosphate pathway, right and left arm of the X, respectively. Fructose-6P is the continuity of glycolysis until pyruvate, as well as the initial compound of the hexosamine pathway, which represent right and left legs of the X, respectively. We evaluated each glucose destination and its regulation, pointing out the products of these pathways and how they can affect synaptic communication. Extracellular L-lactate, either generated from glucose or from glycogen, binds to HCAR1, a specific receptor abundantly localized in perivascular and post-synaptic membranes regulating synaptic plasticity. Methylglyoxal, a product of a deviation of glycolysis, as well as its derivative D-lactate, are also released by astrocytes and bind to GABAA receptors and HCAR1, respectively. GSH, beyond its antioxidant role, also binds to ionotropic glutamate receptors in the synaptic cleft. Finally, we examined the hexosamine pathway and evaluated the effect of GlcNAc-modification on key proteins that regulate the other glucose destinations.